The Development of Property Taxation in Economies in Transition : Case Studies from Central and Eastern Europe - Malme, Jane H. (Washington, DC: World Bank, 2013)
The transition economies of Central and Eastern Europe, through the reform process of decentralization, are now seeking the devolution of fiscal powers, and responsibilities from central, to local governments, within financially sustainable environments. To this end, a system of local budgets, and taxes needs to be devised, over which local governments may have control. Thus, this report focuses on the tax on immovable real property, one of the most important local tax options, and, undertakes comparative analysis of tax policy formulation, within a context of rapid institutional changes. Case studies provide insights into the policy debates, and choices that guide the process of property tax reform, and, shed light on the entire cycle, from initial impetus, to resulting legislation, and the subsequent administrative challenges of assessment, collection, appeal, and review. Because of the multiple roles of property taxation (as an instrument of decentralization, an element of property rights, an adjunct to privatization and restitution, and a source of revenue), it is appropriate to consider its development in multiple contexts. Therefore, the cases range from first generation reformers, i.e., Poland, Estonia, Slovakia, and parts of the Russian Federation, to later efforts in the Czech Republic and Armenia. These cases aim to broaden the understanding of available alternatives, and their relationship to specific political, legal, and economic settings.